Análise de acidentes aéreos associados às condições meteorológicas no Brasil: uma análise sinótica - SOARES, Flávio Mendes (2019)
Through official publications of the Centre for Research and Prevention of Aeronautical Accidents (CENIPA) a quantitative survey was made of aircraft accidents that occurred by contribution of adverse weather conditions in the 1990s. It was observed that most accidents occurred in southern and southeastern of Brazil, during the months of spring and summer. This fact may be associated with atmospheric instabilities that occur due to local conditions and large scale. To try to understand these conditions was made a case study for an incident that occurred in Itaituba/PA on December 18, 1990, where, according to reports of CENIPA, an aircraft had lost control on the ground while performing a landing in conditions with low visibility. For the synoptic analysis of this case, we used data from reanalysis of NCEP / NCAR (National Center for Environmental Prediction / National Center for Atmospheric Research) for long wave radiation (OLR) and zonal (u) and meridional (v) wind levels of 200, 700 and 850 hPa of the atmosphere, GOES 7 satellite images in infrared channel belonging to the NOAA (National Oceanic and Atmospheric Administration). The results showed that there was an interaction of the performance of a frontal system with the circulation of the Bolivian High (AB) and high levels Dug (CAN), which contributed to an intensification of the local effects of convection, which are common on the tropical region.